2003
DOI: 10.1038/sj.onc.1207057
|View full text |Cite
|
Sign up to set email alerts
|

A member of the Pyrin family, IFI16, is a novel BRCA1-associated protein involved in the p53-mediated apoptosis pathway

Abstract: We identified IFI16 as a BRCA1-associated protein involved in p53-mediated apoptosis. IFI16 contains the Pyrin/PAAD/DAPIN domain, commonly found in cell death-associated proteins. BRCA1 (aa 502-802) interacted with the IFI16 Pyrin domain (aa 1-130). We found that IFI16 was localized in the nucleoplasm and nucleoli. Clear nucleolar IFI16 localization was not observed in HCC1937 BRCA1 mutant cells, but reintroduction of wild-type BRCA1 restored IFI16 nuclear relocalization following IR (ionizing radiation). Coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 33 publications
0
95
0
Order By: Relevance
“…Interestingly, IFI16 can also interact directly in vivo with the gene promoter region of both p53 and c-myc [22]. IFI16 has also been shown to bind BRCA1 and this complex has been reported to be involved in the p53-mediated cell death pathway, suggesting that IFI16 may play a role in DNA damage induced apoptosis [23]. However, IFI16 has also been shown to associate with the retinoblastoma tumour-suppressor protein Rb and the transcription factor E2F1, resulting in the inhibition of Rb-E2F1 mediated transcriptional repression [24].…”
Section: Early Research On the Human Pyhinsmentioning
confidence: 99%
“…Interestingly, IFI16 can also interact directly in vivo with the gene promoter region of both p53 and c-myc [22]. IFI16 has also been shown to bind BRCA1 and this complex has been reported to be involved in the p53-mediated cell death pathway, suggesting that IFI16 may play a role in DNA damage induced apoptosis [23]. However, IFI16 has also been shown to associate with the retinoblastoma tumour-suppressor protein Rb and the transcription factor E2F1, resulting in the inhibition of Rb-E2F1 mediated transcriptional repression [24].…”
Section: Early Research On the Human Pyhinsmentioning
confidence: 99%
“…As shown in Fig. 5B, treatment of cells with TSA resulted in increased cleavage of poly(ADP-ribose) polymerase (PARP) protein, which is indicative of caspasemediated apoptosis of cells (31). Consistent with these observations, fluorescence-activated cell sorting analyses of propidium iodide -stained control and TSA-treated LNCaP cells, which resulted in up-regulation of IFI16 protein and down-regulation of AR protein, revealed that TSA treatment significantly increased apoptosis of cells (Fig.…”
Section: Up-regulation Of Ifi16 In Lncap Cells Down-regulates Ar Exprmentioning
confidence: 99%
“…The IFI16 protein binds to the COOH terminus (amino acids 362-393) of p53 (27) and overexpression of the IFI16 protein in cells increases p53 protein levels and stimulates the p53-mediated transcription (25,38). Conversely, knockdown of IFI16 expression results in down-regulation of p53 levels (25).…”
Section: Ifi16 Is a Transcriptional Target Of P53mentioning
confidence: 99%